Positive and Negative Emotions of High School Students in Learning English through Google Classroom - Ningrum, Bunga Ayu; Rokhuma, Chubbi Millatina (Institut Agama Islam Negeri Kudus, 2023)
Google classroom is one of teaching media commonly used by teachers in online English learning system recently. Its use brings various emotions among students. This narrative study aims to explore students’ emotions in learning English through Google Classroom and how these emotions influence English learning. Data were garnered from semi-structure interviews, and analyzed by using the concept from Braun & Clarke. The analysis of the collected data showed that there are positive and negative emotions felt by students, and these emotions influence their English learning. The positive emotions include pleasure, hope, pride, and relief, while the negative emotions include anger, anxiety, shame, hopelessness, and boredom. These emotions in language learning make the students be able to learn all the time (anywhere and anytime) and increase their grades. On the other hand, it also brings them to be reluctant to study, not focus in the learning process, and less interested in learning.